A ANALYSIS OF STUDENTS' ABILITY TO MAKE MATHEMATICAL CONNECTIONS IN SOLVING STORY PROBLEMS INVOLVING INTEGER OPERATIONS AT SMPN 19 PALU FROM THE PERSPECTIVE OF LEARNING STYLES - karmila karmila; Tegoeh S Karniman; Alfisyahra Alfisyahra; Pathuddin Pathuddin (Prima: Jurnal Pendidikan Matematika, 2026)
This study aims to describe the mathematical connection abilities of students with visual, auditory, and kinesthetic learning styles in solving integer operation story problems. This research was conducted at SMP Negeri 19 Palu using a descriptive method with a qualitative approach. The subjects of this study were three seventh-grade students from class VII A, consisting of one student with a visual learning style, one with an auditory learning style, and one with a kinesthetic learning style, as determined through a learning style questionnaire test. The data collection techniques used in this study included learning style tests, written tests, and interviews, which were then analyzed using the Miles and Huberman model, which includes data condensation, data presentation, and conclusion drawing. The data credibility test used in this study was participant validation (member check). The results of this study indicate that students with visual, auditory, and kinesthetic learning styles are able to fulfill all components of students' mathematical connection abilities, connections between mathematical topics, recognizing and applying mathematics in contexts outside of mathematics, and connections between mathematical concepts and the real world or everyday life.